Exploring the Probability of Finding Life in Outer Space: A Convergence of Science and Religion - BELAY SITOTAW GOSHU (Britain International for Academic Research (BIAR) Publisher, 2024)
The search for alien life has captivated people's interest for ages, provoking scientific research, philosophical reflection, and prevalent speculation. This multidisciplinary study explores the possibility of finding life in space by integrating astronomy, astrobiology, philosophy, and theology. The study provides a comprehensive overview of the opportunities and challenges associated with searching for biosignatures, habitability, and the origins of life on Earth. The findings suggest that the galaxy has a potentially habitable exoplanet, making them motivating candidates for additional study. While spectroscopic approaches show promise in finding biosignature chemicals in exoplanet atmospheres, studies of extremophiles shed light on the conditions necessary for life to begin and flourish. It is vital to advance public engagement and education, foster international cooperation, and intensify observational activities. Interdisciplinary collaboration and discussion are crucial to understanding the societal, cultural, and ethical ramifications. The search for alien life, which is still one of humanity's continual efforts to understand the universe and our role in it, is one of the most significant and enduring issues of our day. Through collaborative efforts and persistent inquiry, we might discover evidence of life beyond Earth, fundamentally changing our understanding of the cosmos.